The Pensiangan Muruts: A brief study of their kinship and marriage systems / Hamdan Mohammed - Hamdan, Mohammed (1973)
The pensiangan muruts have experienced some changes in their marriage customs. During the head hunting days even marriage between first cousins was allowed. The two important qualities that the Murut youth had to have in order to marry were strength and courage, for if he wants to marry a girl from his village, he has to give his prospective in-laws the head of an enemy; and if he wants to marry a girl from another village, he has to kidnap the girl and bring her back to his own village. Often this is the cause of inter-village raids. However, with the turn of the century and with European influence slowly creeping deep into country, and especially after the district was made a Government station and administered by a District Officer, the marriage system began to change, and by the time the War came into the area, it was already what it is today. Islam came to Pensiangan in 1970, but it seems to have little impact on the way of life of the Muruts. With a few exceptions, they still hold on to their traditional beliefs and customs.